Experimental research and visualization of modern tectonic movements in the eastern part of the Voronezh crystalline massif (Proceedings of Voronezh State University. Series: Geology, 2020)
Introduction: The article describes the methodology and the results of the experimental studies of modern tectonic movements of the Voronezh crystalline massif (VCM) using deformation monitoring data. It also discusses related issues of modelling natural, technogenic, and ecological systems. Methodology: The study defined the main provisions of the methodology for monitoring and visualizing modern tectonic movements in the form of a vector field based on the results of cyclic geodetic measurements. Results and discussion: It was shown that it is advisable to use the velocities of the displacement vectors of observation points as a key source of information on tectonic movements carried out on large space-time bases. It is not effective to use their absolute values. Conclusions: The experimental data was used to establish the eddy nature of modern tectonic movements as an indicator of active tectonic disturbances.
Keywords: geodynamic movements; deformations; monitoring; visualization; geological structures; vector field; divergence